Analisis Pertanyaan Guru dalam Pembelajaran di SMA Negeri 2 Kerinci Kanan Kabupaten Siak - Supriyadi, Supriyadi; Yuliawan, Tri; Mulyati, Sri (GERAM: Gerakan Aktif Menulis, 2017)
This research entitled "Analysis of Teacher Questions in Learning at SMA Negeri 2 Kerinci Kanan Siak District. The question intended in this study is a stimulus that encourages learners to think and learn (Nasution, 2012: 161). The problem of this research is, What kind of Teacher Question in Learning in SMA Negeri 2 Kerinci Kanan Siak Regency? And how to classify cognitive level questions. This study aims to describe, analyze, interpret, and conclude (1) types of questions; And (2) classification of cognitive level of questions based on bloom taxonomy Teachers in Learning at SMA Negeri 2 Kerinci Kanan Siak District. This study uses the theory of teaching or learning by taking concepts and opinions from various sources. The theory proposed by Zainal Asril (2012), J.J. Hasibuan and Moedjiono (2008), Buchari Alma (2012), Hamid Darmadi (2012), S. Nasution (2012) and Uzer Usman (2010). The results of this study are: first: the type of question used by the type of questions teachers in the process of learning SMA N 2 Kerinci Kanan Siak regency the highest question type of use is the question of digging (J4) as many as 63 questions or (56%), followed by query questions as much as 50 Questions or (44%), while the rhetorical (J2) and directing (J3) type questions are not found or not used by teachers in learning at SMAN 2 Kerinci Kanan Siak District. Second: Question classification used by teacher type in learning process at SMA N 2 Kerinci Kanan Siak Regency according to Bloom's taxonomy are: Knowledge (preccal question) (C1) obtained dta as many as 87 questions or 77%, understanding or comprehension question (C2) of 20 Question or 18%, application or aplication question (C3) not found or not used by teacher in process of learning, analysis or analysis question (C4) as much as 6 question or 5%. The questionnaire of synthetic question questionnaire (C5) and evaluation question (C6) was not found in this study.